The boat - Le, Nam 1979- (Vintage Books, a division of Random House, Inc., 2008)
Stories that take us from the slums of Colombia to the streets of Tehran; from New York City to Iowa; from a tiny fishing village in Australia to a foundering vessel in the South China Sea-- while taking us to the heart of what is means to be human.